Burden of clinical infections due to S. pneumoniae during Hajj: A systematic review. Issue 30 (16th July 2018) - Alqahtani, Amani S.; Tashani, Mohamed; Ridda, Iman; Gamil, Amgad; Booy, Robert; Rashid, Harunor
Abstract: The burden of pneumococcal disease at Hajj has not been precisely evaluated through a systematic review. To this end we have conducted a systematic review on the burden of clinical infections due to Streptococcus pneumoniae among Hajj pilgrims. Major electronic databases including OVID Medline, Web of Science, OVID Embase, Social Sciences Citation Index, Google Scholar and relevant websites (e.g., online Saudi Epidemiology Bulletin) were searched by using MeSH terms and text words containing but not limited to 'Hajj', pneumonia and S. pneumoniae. This was buttressed by hand searching of reference lists of identified studies. Of 21 full text papers reviewed, nine articles were included in this review. Seven studies reported the burden of pneumococcal pneumonia and the other two reported the burden of invasive pneumococcal diseases including meningitis and sepsis. The proportion of pneumonia that was pneumococcal ranged from 1% to 54% of bacteriologically confirmed pneumonias. The pneumococcus accounted for 2/3rd of bacteriologically diagnosed meningitis cases, and 1/3rd of confirmed cases of sepsis. Case fatality rate of pneumococcal pneumonia was recorded in only two studies: 33.3% and 50%. Only one study provided data on antimicrobial susceptibility of S. pneumoniae isolates, reporting 33.3% to be penicillin resistant. None of the included studies provided data on serotype distribution of S. pneumoniae . This systematic review highlights the significance of pneumococcal disease during Hajj, and demonstrates paucity of data on its burden particularly on disease-causing serotype.